ω-3 fatty acids effect on wound healing - McDaniel, Jodi C. (2008)
Physiological events in the initial inflammatory stage of cutaneous wound healing influence subsequent stages. Proinflammatory cytokines coordinate molecular and cellular processes during the inflammatory stage. Polyunsaturated fatty acids (PUFA) alter proinflammatory cytokine production, but how this phenomenon specifically influences wound healing is not clearly understood. In the present study, effects of marine-derived ω-3 eicosapentaenoic and docosahexaenoic PUFA on proinflammatory cytokines in wound serum and time to complete healing in healthy, human skin were evaluated. We compared plasma fatty acid levels in two groups (N=30) at baseline and after 4 weeks of eicosapentaenoic/ docosahexaenoic PUFA supplements (active) or placebo (control). Eight small blisters on participants’ forearms were created. Proinflammatory cytokines interleukin-1β (IL-1β), IL-6, and tumor necrosis factor-α were quantified in blister fluid at 5 and 24 hours after creation. Wound area was calculated daily. Eicosapentaenoic and docosahexaenoic plasma fatty acid levels were significantly higher in the active group. Additionally, we found significantly higher IL-1β levels in blister fluid in the active group and time to complete wound closure was somewhat longer. These results suggest that eicosapentaenoic and docosahexaenoic PUFA may increase proinflammatory cytokine production at wound sites and thus, depending on the clinical context, have noninvasive, therapeutic potential to affect cutaneous wound healing